Caracterización de los principales movimientos de masa presentes en el barrio Zalapa perteneciente al cantón Loja provincia Loja. - Bastidas Ramón, Carlos Vicente (2010)
In this research work we got different results from the field and the laboratory studies that can be taken into account for future research whenever they count with the necessary budget for the different concerning processes. Fieldwork methods were used in this research work such as, the direct observation, in order to recognize the different characteristics which were presented in the area of study and therefore in the manufacture of technical data or specifications of mass movement characterizations obtained in the National University of Loja, Also we use the format for the stocktaking of mass movements version 1.0” used in the “Proyecto Multinacional Andino; Geociencias para las Comunidades Andinas” (PMA-GCA). We also proceeded to make trial pits so that we can know their distribution and determine the local and accurate geology. On the other hand with a topographic station (Trimble 5000 series DR 200) we proceeded to make a topographical drawing of the different mass movements detected in the researched area. For that job we take as a reference a GPS (Global Positional System ) and also a measure of the coordinates UTM in X, Y and Z. Later they were analyzed with the help of software tools (such as ARGIS 9.2 and We have identified that in the Zalapa neighborhood there are 21 mass movements. From these movements we take into account one of them of considerable magnitude. We determined the factors and the outbreaks which affect the mass movements of the area of study. In the laboratory research, through the use of SIG tools as well as the software (ARGIS 9.2), we could develop 13 maps that have been established according to the research done in the area of study, and according to the requirements for obtaining a Susceptibility Map. With the design of different maps we could get some of great importance like the topographic and geologic, but the most outstanding maps are the Stocktaking, slopes, geology, use of the land and isohyets, All of them are necessary to get a Susceptibility Map which will be the final result regarding to maps. In reference to the Susceptibility Map we calculate the value of the low, middle, high and very high areas of susceptibility, in which the area of low susceptibility represents the 4,91%, the area of middle susceptibility the 35,12%, the area of high susceptibility the 44,22% and the area of high susceptibility the 15,75 %. A landslide has been considered for research purposes, taking into account its area. This landslide (DBZ-19) presents an area of 5.1 hectares. Many preventing measures have been established like ditches or verges of coronation, drains and walls that will be explained in detail later in the achievement of this project. Taking as reference the presented characteristics of this research work and the zone, we have developed a Stocktaking Map and a Mass Movement Susceptibility Map. They can be presented to the Society in order to avoid constructions in these areas and therefore the loss of human lives and economical resources.